Kepercayaan Politik dan Partispasi Politik Pemilih Pemula - Akhrani, Lusy Asa; Imansari, Fitsabilla; Faizah, Faizah (Universitas Brawijaya, 2018)
This research aimed to examine the relationship between political trust and political participations among young voters. One hundred and five young voters participated in this quantitative study, sampled by using non-probability sampling (purposive sampling). Data were collected by using Political Trust Scale and Political Participation Scale, both developed by Akhrani (2016). Data obtained from this study were then analysed by using Pearson’s Product Moment technique. The result showed that significant correlation between political trust and political participation do exist (r=0.296, n=105, p=0.002). This result implies that the higher the political trust is, the higher the political participation will be. This study have practical implication that votes from young voters matter significantly for political party as they constitute 20% of overall voters. Therefore, in order to win young voters’ vote, government and political parties should improve their political performance.Penelitian ini bertujuan untuk melihat hubungan antara kepercayaan politik dengan partisipasi politik pada pemilih pemula. Responden dalam penelitian yang menggunakan pendekatan kuantitatif ini adalah 105 orang pemilih pemula, yang diperoleh dengan menggunakan teknik non probability sampling (purposive sampling). Data dikumpulkan dengan menggunakan Skala Kepercayaan Politik dan Skala Partisipasi Politik dari Akhrani (2016). Analisis data penelitian ini menggunakan teknik Product Moment dari Pearson. Hasil dari penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara kepercayaan politik dengan partisipasi politik (r=0.296, n=105, p=0.002). Hal ini bermakna semakin tinggi kepercayaan politik maka akan semakin tinggi pula partisipasi politiknya. Penelitian ini memberikan implikasi praktis bahwa suara para pemilih pemula sangat penting bagi partai politik karena jumlahnya yang mencapai 20% dari keseluruhan suara pemilih. Dengan demikian, untuk mendapatkan suara para pemilih pemula, pemerintah dan partai politik harus memperbaiki kinerja politiknya.